2016
DOI: 10.1111/nph.14056
|View full text |Cite
|
Sign up to set email alerts
|

Symbiodinium sp. cells produce light‐induced intra‐ and extracellular singlet oxygen, which mediates photodamage of the photosynthetic apparatus and has the potential to interact with the animal host in coral symbiosis

Abstract: SummaryCoral bleaching is an important environmental phenomenon, whose mechanism has not yet been clarified. The involvement of reactive oxygen species (ROS) has been implicated, but direct evidence of what species are involved, their location and their mechanisms of production remains unknown.Histidine-mediated chemical trapping and singlet oxygen sensor green (SOSG) were used to detect intra-and extracellular singlet oxygen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 69 publications
(117 reference statements)
5
62
0
Order By: Relevance
“…Under these circumstances, as indicated here, there may be side effects on cyclic electron transport and the Mehler-AscorbatePeroxidase (MAP) pathway. Recent works (Reynolds et al, 2008;Roberty et al, 2014;Aihara et al, 2016) have indicated the possibility that singlet oxygen production is generated when PQ pool is reduced, i.e., the relative size of oxidized PQ pool is smaller (and thus charge recombination in PSII reaction centers is promoted), which may be a primary factor in coral bleaching (Vass, 2012;Rehman et al, 2016). Nevertheless, these effects have to be documented individually in corals, where it is known that there are varied responses to similar acute thermal stress scenarios (Downs et al, 2013;Gardner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, as indicated here, there may be side effects on cyclic electron transport and the Mehler-AscorbatePeroxidase (MAP) pathway. Recent works (Reynolds et al, 2008;Roberty et al, 2014;Aihara et al, 2016) have indicated the possibility that singlet oxygen production is generated when PQ pool is reduced, i.e., the relative size of oxidized PQ pool is smaller (and thus charge recombination in PSII reaction centers is promoted), which may be a primary factor in coral bleaching (Vass, 2012;Rehman et al, 2016). Nevertheless, these effects have to be documented individually in corals, where it is known that there are varied responses to similar acute thermal stress scenarios (Downs et al, 2013;Gardner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress inhibits the repair of photosystem II (Takahashi et al, 2009) and lowers the photoinhibitory threshold of the symbiotic algae (Jones et al, 1998;Warner et al, 1999;Bhagooli and Hidaka, 2003;Takahashi et al, 2009), thereby facilitating light-induced damage to Photosystem II reaction centers, particularly the D1 protein (Aro et al, 1993). The resulting faults in energy transfer and electron transport can lead to oxidative stress (reviewed by Pospíšil, 2016) that can cause the breakdown of the symbiotic association and loss of algal cells from the coral tissue (Lesser, 1997;Rehman et al, 2016). The susceptibility of corals to heat and light stress-induced bleaching is increased by unfavorable levels of nutrients in the water, in particular by phosphate deficiency (D'Angelo and Wiedenmann, 2014;Rosset et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent probes have been used previously to detect both intracellular and extracellular reactive nitrogen and oxygen species in the Family Symbiodiniaceae (Lesser ; Bouchard and Yamasaki ; McGinty et al ; Roberty et al ; Rehman et al ; Wietheger et al ). Here, fluorescent probes specific for 1 O 2 and O 2 − and a general ROS/RNS probe that can detect H 2 O 2 , O 2 − , and ONOO − (Lesser ; Rehman et al ) were used to measure the relative intracellular differences due to treatment effects, with the fluorescence signal for each probe being proportional to concentration, for these ROS/RNS using a dual laser, four color, Beckton‐Dickinson FACSCalibur flow cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent probes have been used previously to detect both intracellular and extracellular reactive nitrogen and oxygen species in the Family Symbiodiniaceae (Lesser ; Bouchard and Yamasaki ; McGinty et al ; Roberty et al ; Rehman et al ; Wietheger et al ). Here, fluorescent probes specific for 1 O 2 and O 2 − and a general ROS/RNS probe that can detect H 2 O 2 , O 2 − , and ONOO − (Lesser ; Rehman et al ) were used to measure the relative intracellular differences due to treatment effects, with the fluorescence signal for each probe being proportional to concentration, for these ROS/RNS using a dual laser, four color, Beckton‐Dickinson FACSCalibur flow cytometer. Three probes were utilized to detect ROS/RNS; 2′,7′‐dichlorofluorescein‐diacetate (H 2 DCFDA ex: 488 nm/em: 515–555 nm), 25 μ L of a 1 mM solution (in 5 mM DMSO) to 250 μ L of culture and incubated for 5 min at room temperature in the dark to detect intracellular H 2 O 2 , O 2 − , and ONOO − (Lesser ), hydroethidine (HE ex: 488 nm/em: 560–570 nm), 25 μ L of a 250 μ M solution (in 5 mM dimethyl sulfoxide [DMSO]) to 250 μ L of culture and incubate for 15 min at room temperature in the dark to detect intracellular O 2 − formation (Lesser ; Zhao et al ) and Singlet Oxygen Sensor Green (SOSG ex: 504 nm/em: 525 nm) 25 μ L of a 250 μ M solution (in 100 mM Tris, pH 7.5) to 250 μ L of culture and incubate for 15 min at room temperature in the dark to detect intracellular 1 O 2 formation (Rehman et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation